Proprioceptive rehabilitation in acl injury associated with medial menisco (Research, Society and Development, 2021)
The knee joint is a structure formed by the union of three bones: femur, tibia and patella (sesamoid bone). In general, the knee consists of a complex bone, articular, ligament, capsular, meniscal and muscular structure, capable of promoting stability and changing the ground irregularities from a flexible structure to a rigid one for weight-bearing. Knee stability is provided by the restraining mechanism of the anterior and posterior cruciate ligaments, medial and lateral collateral ligaments, which are essential for efficient human locomotion. It refers to a study carried out on the subject through national and international bibliographical references, periodicals, books, newspapers and scientific journals. The selected searches were from 1992 to 2011, and were available for online access. The selected articles were evaluated by the author of the research, and those that did not fit the proposed theme were disregarded. Signs and symptoms of knee ligament injuries vary according to the causative mechanism, the severity of the injury, the tissues involved and the extension of the involvement. Variable degrees of pain, joint effusion, insecurity and disability are usually evident. In conclusion, based on the study carried out, it was found that, according to the authors investigated, proprioceptive training is efficient in the rehabilitation of anterior cruciate ligament and lateral meniscus injuries, thus promoting improved stability and functional capacity, providing early improvement. safety and return to activities of daily living in a satisfactory manner.